Gendered Patterns in Teacher-Student Interaction in EFL Classroom: The Greek Context - Stella Minasyan (National Research University Higher School of Economics, 2017)
The present research endeavours to shed light on the role that gender plays in the language classroom in the Greek context. As no systematic investigation has considered special aspects of gender and interaction in primary school classrooms, this study seeks to investigate how teachers and students position themselves within different discourses in EFL classroom interaction. The issues discussed include turn-taking and interruptions, praise and reprimand, class dominance, teacher attention and class participation in classroom interaction. Drawing on language and gender research, it was hypothesized that gender of the learner affects the learner's language use and behaviour during EFL interaction. This study advances our understanding of gendered classroom interaction and highlights important ways in which students' gender influences teacher-student, as well as student-student interaction. Moreover, this study sheds light on gender bias which occurs in the classroom and thus impedes teachers' abilities to work successfully with all students. The Greek data revealed great similarity with findings of previous studies by supporting the assumption that: (a) teachers are biased in favour of boys, especially with respect to giving them more attention; (b) male students demand more teacher attention and more instructions from the teacher than their female peers; (c) female students are more likely to receive praise and positive comments, whereas male students are reprimanded by the teacher; (d) male students are more active in class participation, by taking more turns, volunteering and calling out.